The Technology Acceptance Model of Mobile Payment Usage on Generation Z - Nerry Kristina; Ibnu Harris (Binus Business Review, 2020)
The research aimed to support Technology Acceptance Model (TAM) theories such as Perceived Ease ofUse (PEOU), Security (SECU), Brand Loyalty (BL), Behavioural Intention (BI), and the marketing models,Electronic Word of Mouth (EWOM), on the use of mobile payments of the Generation Z. The researchers usedthe quantitative method. Using a non-probability sampling method with a convenience sampling technique, therewere 100 respondents of Generation Z. The data were then analyzed using Structural Equation Modeling (SEM)with Partial Least Square (PLS). The results show that PEOU has no significant effect on BI. SECU and BL affectBI significantly. Then, BI has a significant impact on EWOM. It means that PEOU is not an important factor forGeneration Z to use mobile payment. SECU and BL make the Generation Z continue to use mobile paymentwithout worrying about data privacy issues because BL is embedded in their mind. As a result of BI, GenerationZ will do marketing in the form of EWOM to their closest friends or relatives via social media.